2022
DOI: 10.1111/jce.15713
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed field ablation in patients with complex consecutive atrial tachycardia in conjunction with ultra‐high density mapping: Proof of concept

Abstract: Introduction Catheter‐ablation (CA) of consecutive left atrial tachycardias (LAT) can be challenging. Pulsed field ablation (PFA) yields a novel nonthermal CA technology for treatment of atrial fibrillation (AF). There is no data regarding PFA of LAT. This study sought to investigate PFA of consecutive LAT following prior CA of AF. Methods Consecutive patients with LAT underwent ultrahigh‐density (UHDx) mapping. Subsequent to identification of the AT mechanism, PFA was performed at the assumed critical sites f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…14 This finding was confirmed in other studies and a more detailed analysis showed that the PV size may play a significant role, with larger PVs showing more reconnections and the superior PVs being commonly larger in diameter than their inferior counterparts. 28,29 Since both the 31-mm and 35-mm FARAWAVE catheters usually cover the whole PV-ostium, the reasons for more reconnections of larger-diameter PVs are not obvious and need further research. The density of the electric field at different distances from the catheter might play a role.…”
Section: Outcomementioning
confidence: 99%
“…14 This finding was confirmed in other studies and a more detailed analysis showed that the PV size may play a significant role, with larger PVs showing more reconnections and the superior PVs being commonly larger in diameter than their inferior counterparts. 28,29 Since both the 31-mm and 35-mm FARAWAVE catheters usually cover the whole PV-ostium, the reasons for more reconnections of larger-diameter PVs are not obvious and need further research. The density of the electric field at different distances from the catheter might play a role.…”
Section: Outcomementioning
confidence: 99%
“…Its current field of application is mostly AF ablation, e.g., PVI, 15) but other ablation approaches in the atria or ventricles have been investigated in animal models 16) 17) 18) 19) and as an off-label use in humans. 20) 21) 22) The technique utilizes high amplitude pulsed electrical fields that are exposed to sensitive myocardial cells, which leads to subsequent cell death through the mechanism of irreversible electroporation (IRE). Electroporation acts by increasing the permeability of the cell membrane after exposure to electric fields.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of the journal, Gunawardene and co-workers present their early experience with PFA for the treatment of patients with post-AF ablation atrial tachycardia (AT) (4). Their analysis includes 15 patients with a history of multiple AF/AT ablation procedures.…”
mentioning
confidence: 99%